Selected Aspects of the Residential Property Market in the Context of Creating a City Image (an Example from Rzeszów) - Kuźniar, Wiesława; Cyran, Kazimierz (Olsztyn Economic Journal, 2020)
The main goal of the article is to evaluate the city’s real estate sub-product and identify the impact of perception of this urban sphere on the overall image of Rzeszów city among students. A thesis was accepted by the authors that the attractive image of Rzeszów determines the development of the residential real estate market, attracting especially young, educated people to the city. On the basis of a literature analysis of the subject, information obtained from secondary sources on the topic of Rzeszów, as well as surveys carried out in 2018 among students (n = 325), the thesis was confirmed. Thanks to the fast, modern development of the city and consistently implemented marketing activities, Rzeszów is perceived as an innovative city that is friendly to residents, investors and students. This contributes to the inflow of new, usually young, educated residents and investors, which in turn translates into high dynamics in the residential real estate market. Questionnaire surveys carried out among students have shown that they highly appreciate the current image of Rzeszów and, most after graduation, plan to stay in the city which in their opinion is an attractive place for everyday life.